A Review on Biological and Medicinal Significance of Furan - Hana Saeid; Hadeel Al-sayed; Marwa Bader (AlQalam Journal of Medical and Applied Sciences, 2023)
An important group of heterocyclic compounds with significant biological characteristics are furan derivatives. The creation of furan derivatives and their testing for various pharmacological properties have received a lot of attention over the past few decades. Various substances with anti-bacterial properties have a fundamental skeleton made up of furan rings. These molecules are frequently used in antiviral, antifungal, anti-inflammatory, analgesic, antidepressant, anti-anxiolytic, anti-parkinsonian, anti-glaucoma, muscle relaxant, antihypertensive, diuretic, anti-ulcer, anti-ageing, and anticancer medications. The biological activity of furans can alter noticeably due to a slight modification in the pattern of substitution. In the realm of medicinal chemistry, furan derivatives have taken on a special position. An important synthetic technique in the search for new drugs is the inclusion of the furan nucleus. The great therapeutic efficacy of furan-related medicines has promoted the medicinal chemists to create large number of novel chemotherapeutic agents. The field of medicinal chemistry encompasses a diverse array of opportunities due to the different ways that furans derivatives can be synthesized as well as their various structural reactions. This article aims to review previous work on the medicinal and biological activities during past years.